Children Who Attend Formal Day Care Do Better in School: Even Many Years Later in Secondary School - C. Katharina Spieß; Charlotte Büchner (Weekly Report, 2009)
Questions about the advantages and disadvantages of sending young children to formal day care ("Kindertageseinrichtungen") have always greatly concerned parents and led to intense, if not always well informed, policy debate. Two issues have been foremost. One is whether young children removed from their parents' care for part of the day suffer long term emotional consequences, or whether on the contrary, interaction with other children and with carers improves their social skills and confidence. Results are generally positive for children over three years old, but mixed for children under three, with some studies indicating negative socio-emotional consequences (Rossbach, 2005), and others reporting no negative emotional results and clear gains in social competence (Tietze, 1998; Andersson, 1989, 1992; NICHD, 2000, 2001). The second issue, dealt with in this article, relates to children's school outcome. Do children who have been to formal day care which exposes them to some pre-school learning achieve better, the same, or worse educational results in their later school years? If they do better, how long does the advantage last? Does it persist through to secondary school?
Keywords: 330